PENGUATAN KETERAMPILAN MASYARAKAT MELALUI DIVERSIFIKASI PRODUK NUGGET DAN SUMPIA BERBAHAN DASAR KEPITING BAKAU (Scylla spp.) - Handayani; Muh. Kasim; Muhamad Ali Ulat; Asthervina Widyastami Puspitasari (Buletin SWIMP, 2021)
The low grade of mud crab caught causing market crashes. The aim of this activity was to improve the skills of local partners in processing low-grade mud crab to be more valuable. This activity was a collaboration between Sorong Polytechnic of Marine and Fisheries and Conservation International using demonstration and direct instruction model through training on the processing of nugget and sumpia based mud crab with 10 participants from Komplek Rimba Pala, Jalan Mandiri RT. 06, RW. 06, District Remu Selatan, Sorong City, Papua Barat Province. Post-test which part of the evaluation, it was shown an increase in the knowledge and skill possess by the local partner.